Partisipasi Masyarakat Pesisir dalam Melestarikan Hutan Mangrove di Kecamatan Pasir Sakti Kabupaten Lampung Timur - Al Safar, M Rizki; Gultom, Dame Trully; Riantini, Maya (Suluh Pembangunan : Journal of Extension and Development, 2024)
The purpose of this study was to analyze the level of community participation in activities to preserve mangrove forests and to analyze factors related to community participation in preserving mangrove forests in Pasir Sakti District, East Lampung. The research method used in this study was a survey method, then the collected data was tabulated based on each category and analyzed descriptively and Spearman Rank test. The conclusion is that the level of community participation in activities to preserve mangrove forests involving processes that include planning, implementation and evaluation is in the medium category, and the utilization of the results is in the high category. Factors related to community participation in preserving mangrove forests are level of non-formal education, type of work, number of family dependents, length of stay, distance of house from mangrove location, role of community leaders, role of farmer groups, government support, and role of non-governmental organizations. government organization, while the factors that are not related are age and level of education. Keywords: participation, participation factor, mangrove forest